2018
DOI: 10.1039/c8ra05250f
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic delivery of bFGF and BMP-2 from poly(l-lactic-co-glycolic acid)/graphene oxide/hydroxyapatite nanofibre scaffolds for bone tissue engineering applications

Abstract: One of the goals of bone tissue engineering is to create scaffolds with excellent biocompatibility, osteoinductive ability and mechanical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…Bhahat et al applied solution blending to introduce GO and HAP into collagen and fabricated Col/GO/HAP nanocomposite scaffold via freeze drying, and found that the compressive stress and biocompatibility were improved [15] . Renet al implemented solution blending to introduce GO and HAP into poly (L-lactic-co-glycolic acid) (PLGA) and fabricated PLGA/GO/HAP nanofibre scaffold via electrospinning, and discovered that the tensile strength and cytocompatibility were improved [16] . Xiong et al treated HAP with glucosamine and then blended it with GO and sodium alginate (SA) to fabricate GO/HAP/SA nanocomposite scaffold through freeze drying, and found that the compressive properties and bioactivity of the scaffold were better than those of neat SA scaffold [17] .…”
Section: Introductionmentioning
confidence: 99%
“…Bhahat et al applied solution blending to introduce GO and HAP into collagen and fabricated Col/GO/HAP nanocomposite scaffold via freeze drying, and found that the compressive stress and biocompatibility were improved [15] . Renet al implemented solution blending to introduce GO and HAP into poly (L-lactic-co-glycolic acid) (PLGA) and fabricated PLGA/GO/HAP nanofibre scaffold via electrospinning, and discovered that the tensile strength and cytocompatibility were improved [16] . Xiong et al treated HAP with glucosamine and then blended it with GO and sodium alginate (SA) to fabricate GO/HAP/SA nanocomposite scaffold through freeze drying, and found that the compressive properties and bioactivity of the scaffold were better than those of neat SA scaffold [17] .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, bone tissue engineering shows great potential in developing effective alternative as bone substitutes and grafts for bone defect repair. Various synthetic and natural materials, including polycaprolactone, PLGA, bioactive glasses, and chitosan, have been fabricated potential bone scaffolds that are utilized as grafts for bone defect repair [4][5][6][7]. For PLGA materials in particular, many researchers have fabricated PLGA scaffolds for bone defect repair; they show good biocompatibility, low immunogenicity, and toxicity and are widely used in pharmaceutical and tissue engineering as an FDA certificated medical materials.…”
Section: Introductionmentioning
confidence: 99%
“…Compare with graphene and rGO, GO has better dispersion within the polymer. Previous studies reported that the mechanical properties of polymer materials were improved by the addition of GO due to the interfacial interaction between the oxygen containing functional moieties of GO and the hydroxyl or amine groups of the polymer materials [5,15,34]. After PLL surface modification, it could be seen that there was no statistically significant difference in the tensile strengths of all hybrid fiber matrices before and after PLL surface modification, which indicated that the mechanical properties of hybrid fiber matrices appeared not to have been affected by the PLL surface modification.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Zhou et al [44] investigated the potential of poly(D,L-lactic acid)/collagen/ HAp composite nanofibers for bone regeneration. Ren et al [45] fabricated the electrospun poly(L-lactic-coglycolic acid)/HAp/graphene oxide for bone tissue engineering. However, there was no report about incorporation of DOX-HAp into the PVA-chitosan/PU core-shell nanofibers for bone cancer treatment in vitro.…”
Section: Introductionmentioning
confidence: 99%